The proposed role of ultrasound in the management of giant cell arteritis in routine clinical practice. (16th October 2017) - Monti, Sara; Floris, Alberto; Ponte, Cristina B; Schmidt, Wolfgang A; Diamantopoulos, Andreas P; Pereira, Claudio; Vaggers, Sophie; Luqmani, Raashid A.
Abstract: Objective: To develop and explore a protocol for using colour duplex sonography (CDS) in the routine care of GCA. Methods: We tested CDS of temporal arteries and axillary arteries (AXs) on consecutive patients with suspected or established GCA, between July 2014 and September 2016. Results: We assessed 293 patients [age 72 (10), female/male 196/97], of whom 118 had clinically confirmed GCA. Seventy-three percent of patients had already received high-dose glucocorticoids (GCs) for 17 (33) days. Among new referrals with <7 days of GC treatment ( n = 55), the sensitivity of CDS was 63.3% (95% CI: 44%, 80%), specificity 100% (95% CI: 83%, 100%), positive predictive value 100% and negative predictive value 64.5% (95% CI: 53%, 74%). Sensitivity rose to 81.8% in patients with jaw claudication and high inflammatory markers. During the observation period, the rate of temporal artery biopsies decreased from 72 (42%) to 36 (25%) ( P = 0.002). CDS was positive in 21% of 89 follow-up scans in asymptomatic individuals, compared with 37% in patients experiencing clinical flares. Over time, the number of halos reduced; only new or flaring patients showed a halo in four or more sites. The diameter of axillary halos reduced from referral [1.6 (0.4) mm] to follow-up [1.4 (0.2) mm, P = 0.01] or flares [1.4 (0.2) mm, P = 0.02]. Conclusion: CDS provides high positive predictive value for diagnosing GCA and allows for a significant reduction in temporal artery biopsies. We explored the role of CDS in detecting flares and demonstrated a relationship to the extent of the distribution of halos, but not to their size.